Analysis of Variation in Iron Coating Rubber for Upper Punch Moulds: Analisa Variasi Karet Pelapis Besi untuk Mould Upper Punch - Wahyu, Rizky; Iswantoi, Iswantoi (Procedia of Engineering and Life Science, 2024)
This study investigates the evolution of ceramic mold design and manufacturing processes, focusing on the role of punches in shaping ceramics through injection molding techniques. Key findings reveal diverse punch types—isostatic, pressure rubber, and exhaust punches—tailored to meet varying market demands. By employing ASTM 1045 high-performance 45 steel, we explore the impact of these punches on product quality and efficiency. Qualitative research methods, comprising literature review, observations, and interviews, were utilized to analyze the production process, formulation of ceramic bodies, and variations within ceramic molding tools and procedures. Our work contributes valuable insights into the advancements of injection molding technology, particularly in the context of rapid growth in polymeric materials' usage and their potential for mass production via fast cycle times and high quantities. Highlight : Diverse punch types tailored to meet market demands, including isostatic, pressure rubber, and exhaust punches Utilization of ASTM 1045 high-performance 45 steel for improved product quality and efficiency Employment of qualitative research methods, such as literature reviews, observations, and interviews, to examine the production process, ceramic body formation, and tool variations Keywords: ceramic mold, punches, injection molding, ASTM 1045 steel, diversified punches, qualitative analysis